Astronomy in Ancient Egypt - Quack, Joachim Friedrich (The Oxford handbook of science and medicine in the classical world, 2018)
This chapter studies Egyptian astronomy based on the very few surviving texts. The Egyptian calendar was purely solar, unlike most ancient calendars. The oldest astronomical monuments from Egypt are the star clocks, mainly on the interior of coffin lids from the Eleventh and Twelfth Dynasties. They divide the year into 36 ten-day intervals (decades), each with 12 stars, to mark the hours of the night for religious purposes. The major text of Egyptian astronomy is the Book of Nut, the sky goddess, which describes the behavior of the sun, moon, and especially fixed stars, as well as shadow clocks and water clocks. The Egyptian constellations were fundamentally different from ours (based on Mesopotamian and Greek myths), with Osiris (our Orion), Seth (our Big Dipper), and Sirius playing a prominent role, plus the Ship, the Sheep, and the Two Tortoises. Late Egyptian astronomy borrows some techniques from Mesopotamian astronomy. In the Greco-Roman period, Egyptian astronomy borrows elements from Greco-Roman astronomy.